2011
DOI: 10.1007/s10517-011-1485-7
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic postconditioning and size of myocardial infarction during inhibition of norepinephrine reuptake

Abstract: We studied the effect of inhibition of norepinephrine reuptake during the reperfusion period on the size of infarction zone after focal myocardial ischemia and under conditions of ischemic postconditioning. In groups 1 and 2, 30-min occlusion of the left coronary artery followed by 120-min reperfusion was performed. In groups 3 and 4, ischemia was followed by ischemic postconditioning (six 10-sec occlusions alternating with 10-sec reperfusions). Ringer solution (1 ml, groups 1 and 3) and desipramine (0.8 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…As a matter of fact, the timing of norepinephrine uptake inhibition relative to MI onset is critical for its cardioprotective effect since norepinephrine accumulates in the extracellular space rapidly after ischemia onset (Fujii et al, 2004), which enhances cardiac work (Zhou et al, 2012) and can be harmful to the ischemic myocardium. Indeed, Naumenko et al (2011) observed that desipramine administration at the onset of reperfusion is associated with a significant increase in infarct size. We speculate that DV could have better cardioprotective properties than desipramine, even when treatment is started after the onset of reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, the timing of norepinephrine uptake inhibition relative to MI onset is critical for its cardioprotective effect since norepinephrine accumulates in the extracellular space rapidly after ischemia onset (Fujii et al, 2004), which enhances cardiac work (Zhou et al, 2012) and can be harmful to the ischemic myocardium. Indeed, Naumenko et al (2011) observed that desipramine administration at the onset of reperfusion is associated with a significant increase in infarct size. We speculate that DV could have better cardioprotective properties than desipramine, even when treatment is started after the onset of reperfusion.…”
Section: Discussionmentioning
confidence: 99%